Family Challenges in the Indonesia-Malaysia Border Areas: Early Marriage, Child Violence, and Stunting in Sambas Regency - Suratman, Bayu; Arif, Mahmud; Purnama, Sigit (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
The rise of early marriage, child violence, and stunting that occur in Indonesia are problems and challenges in building family welfare. This study delves into the significant family challenges in Sambas Regency, West Kalimantan Province, Indonesia, bordering Malaysia. It focuses on three critical issues: early marriage, child violence, and stunting. Using a qualitative descriptive approach, we gathered data through interviews, observations, and documentation, ensuring accuracy with triangulation methods. The findings are quite alarming. Early marriage rates are high, with 563 cases involving teenagers aged 15-19 in 2022 alone. Child violence, particularly sexual abuse, remains a grave concern, with 101 cases reported over the past three years. Stunting, which hampers early childhood development, affects 30.5% of children, especially in urban areas. These challenges underscore the urgent need for integrated policies that address economic, educational, and social factors to support family welfare. While our study has limitations, such as relying on reported cases and being cross-sectional, it lays the groundwork for future research and policy-making. We recommend adopting longitudinal and comparative studies to better understand regional differences and causal factors. Tackling these issues requires a sustained, multifaceted approach and collaborative efforts from all stakeholders. Together, we can create a supportive environment for families, break the cycle of poverty, and promote sustainable development in border areas.